Nitric oxide-inhibited chloride transport in cortical thick ascending limbs is reversed by 8-iso-prostaglandin-F2α - Pablo D. Cabral; Guillermo B. Silva; Sandra T. Baigorria; Luis I. Juncos; Ebenezer I. O. Ajayi; Néstor H. García (The Korean Society of Nephrology, 2022)
Background Sodium chloride (NaCl) reabsorption in the cortical thick ascending limb (cTAL) is regulated by opposing effects. Nitric oxide (NO) inhibits NaCl reabsorption while 8-iso-prostaglandin-F2α (8-iso-PGF2α) stimulates it. Their interaction has not been evaluated in the cTAL. Because 8-iso-PGF2α has considerable stability while NO is a free radical with a short half-life, we hypothesized that, in the cTAL, the inhibition of NaCl absorption will be reversed by 8-iso-PGF2α. Methods Chloride absorption (JCl) was measured in isolated perfused cTALs and whether the activation of protein kinase A (PKA) is required for this interaction. Since cyclic adenosine monophosphate (cAMP) is a major messenger for the 8-iso-PGF2α signaling cascade, and NO inhibits JCl by decreasing cAMP bioavailability, we measured 8-iso-PGF2α-stimulated cAMP in the presence of sodium nitroprusside (SNP). Results The NO donor, SNP (10-6 M), decreased JCl by 41%, while luminal 8-iso-PGF2α (100 μM) increased JCl to 315 ± 46 pmol/min/mm (p < 0.003), reversing the effects of the NO donor. SNP inhibited JCl, 8-iso-PGF2α failed to increase JCl in the presence of H89. Basal cAMP was 56 ± 13 fmol/min/mm, in the presence of SNP 57 ± 6 fmol/min/mm, and 8-iso-PGF2α increased it to 92 ± 2 fmol/min/mm (p < 0.04). Conclusion We concluded that 1) NO-induced inhibition of JCl in the cTAL can be reversed by 8-iso-PGF2α, 2) 8-iso-PGF2α and NO interaction requires PKA to control JCl, and 3) in the presence of NO, 8-iso-PGF2α continues to stimulate JCl because NO cannot reverse 8-iso-PGF2α-stimulated cAMP level.